(untitled) (ELEKTRIKA- Journal of Electrical Engineering, 2019)
This paper presents the design of compact wideband frequency reconfigurable metamaterial (MTM) antenna. The design is based on the idea of obtaining single and multi-bands in wideband metamaterial antenna within the range of bandwidth. This is achieved by introducing capacitive slots which neutralize inductive properties and generate left handed capacitive parameter. The three series slots in the patch contribute for bandwidth enhancement while two PIN Diode Switches provide multi-bands operation. Computer Simulation Technology (CST) software is used to determine the operation and effectiveness of the proposed antenna. The approach has several notable merits which include improvement of spectrum utilization, minimize spectrum congestion, interference and provide bands selectivity. Â From the simulation results, it was found that, bandwidth was improved to 2.8 GHz which is equivalent to 82% fractional bandwidth. Also, it can switch to seven different frequency bands of operation with only two number of switches. The realized peak gain is 2.44 dBi and 3.15 dBi at 2.4 GHz and 5.0 GHz respectively with average efficiency of 95%. The antenna can be utilized for wireless communication and cognitive radio application.